An investigation into the exercise behaviours of regionally based Australian pregnant women. Issue 8 (August 2016) - Hayman, Melanie; Short, Camille; Reaburn, Peter
Abstract: Objectives: Regular exercise during pregnancy is a recommended prenatal care strategy with short and long-term health benefits to mother and child. Unfortunately, most pregnant women are insufficiently active to obtain health benefits and there is evidence that activity levels decrease overall during pregnancy. Physical activity among regionally based women is lower than that of urban-based women within Australia. However, little is currently known about exercise behaviours of regionally based Australian pregnant women. To successfully promote exercise among regionally based pregnant women, a greater understanding of exercise behaviours must first be explored. This study investigated exercise behaviours in a sample of regionally based Australian pregnant women. Design: Regionally based Australian pregnant women ( n = 142) completed a modified version of the Godin Leisure-Time Exercise Questionnaire examining exercise behaviours before and during pregnancy. Methods: Women self-reported their exercise behaviours, including exercise frequency, intensity, time and type, before and during pregnancy. Results: Chi-square analysis revealed significantly less ( χ 2 = 31.66, p < 0.05) women participated in exercise during pregnancy (61%) compared to before pregnancy (87%). During pregnancy, respondents exercised at a significantly lower frequency ( χ 2 = 111.63, p < 0.05), intensity ( χ 2 = 67.41, p < 0.05), shorter time/duration ( χ 2 = 114.33, p < 0.05), and significantly less ( χ 2 = 8.55, p < 0.05) women (8%) are meeting 'exercise during pregnancy' guidelines compared to women before pregnancy (49%) meeting physical activity guidelines. Conclusions: Exercise during pregnancy decreases to levels significantly lower than what is currently recommended. Public health initiatives that promote exercise among Australian pregnant women should aim to increase frequency, intensity, time and type of exercise to be undertaken during pregnancy.